Manajemen Pendekatan Pendidikan Untuk Meningkatkan Kualitas Pendidikan - Nabila Zulfa; Dita Oktaviani; Tasya Widyana; Hasbih Sholeh Suryadi; M. Muflih Dermawan; Maulidayani M (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The importance of approaches and methods in education, educators demand professionalism in developing these approaches and methods. This research aims to make improvements to achieve quality education. This research uses a qualitative approach, the process of organizing, analyzing and interpreting non-numerical data (words) into information. The data collection technique was carried out through an interview technique process. Meanwhile, the research subject was the Principal of Mts. Mualimin Univa. The research results show that: Improving the quality of education is a process that is integrated with the process of improving the quality of human resources themselves.Â